DNA dosimeter measurements of beam profile using a novel simultaneous processing technique. (November 2020) - Bui, B.; McConnell, K.; Obeidat, M.; Saenz, D.; Papanikolaou, N.; Shim, E.Y.; Kirby, N.
Abstract: A DNA dosimeter (DNAd) was previously developed that uses double-strand breaks (DSB) to measure dose. This dosimeter has been tested to measure dose in scenarios where transient-charged particle equilibrium (TCPE) has been established. The probability of double strand break (PDSBo ), which is the ratio of broken double-stranded DNA (dsDNA) to the initial unbroken dsDNA in the dosimeter, was used to quantify DSBs and related to dose. The goal of this work is to produce a new technique to process and analyze the DNAd and quantify DNA-DSBs. This technique included simultaneously processing multiple DNAds and also establishing a new form to the probability of double strand break (PDSBn ), which was then used to test the DNAd in a non-TCPE condition by taking beam penumbra measurements. The technique utilized a 384-well plate, and the measurements were made at the edge of a 10 × 10 cm field and compared to film measurements. During these penumbra measurements, while observing the positional differences in the higher gradient region at 4.1 and 4.55 cm from the center of the radiation field, the distance to agreement of PDSBo to film were 0.38 cm and 0.26 cm while the distance to agreement of PDSBn to film were 0.11 cm and 0.06 cm, respectively. Finally, the developed new separation technique reduced the time needed for the analysis of 25 samples from 200 min to 30 min. Highlights: A new DNA dosimeter analysis technique was developed here that drastically reduces the processing time for these devices. This technique was utilized to make beam penumbra measurements. The DNA dosimeter produces similar predictions for beam penumbra dose measurements as conventional devices. These are critical steps to improve and validate the DNA dosimeter as a radiation dose measurement technique.